A lithium iron manganese phosphate positive electrode material and preparation method thereof

By using intercepting film materials composed of phenol nanocellulose and SiO2-nanotubes in lithium manganese iron phosphate positive electrode material, the dissolution of Mn2+ is prevented, and the problem of high dissolution rate of Mn2+ is solved, and the cycle life and electrochemical performance of the battery are improved.

CN119361660BActive Publication Date: 2025-03-25HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411897392.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The dissolution rate of Mn2+ in lithium manganese iron phosphate positive electrode material is high during the battery cycle, resulting in the hindered insertion and deintercalation of manganese ions, destroying the SEI film, and affecting the cycle life of the battery.

Method used

Using 85-95 parts of LiMn(1-X)FeXPO4 and 3-8 parts of intercepting membrane material, the intercepting membrane material consists of phenol nanocellulose and SiO2-nanotubes. A thin film is formed by vacuum suction filtration and fixed on the surface of the carbon cladding layer to prevent the dissolution of manganese ions.

Benefits of technology

It effectively reduces the dissolution rate of Mn2+, enhances the mechanical strength of the carbon coating, and improves the cycle life and electrochemical properties of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361660B_ABST
    Figure CN119361660B_ABST
Patent Text Reader

Abstract

The invention discloses a lithium manganese iron phosphate positive electrode material and a preparation method thereof, which relates to the technical field of lithium ion batteries, including LiMn (1‑X) Fe X PO4 and interception membrane material; wherein the interception membrane material comprises phenolic nanocellulose and SiO2-nanotubes; LiMn (1‑X) Fe X The surface of PO4 has a carbon coating layer, and the interception membrane material is fixed on the surface of the carbon coating layer in the form of a thin film, which can improve the mechanical strength of the carbon coating layer and prevent the dissolution of manganese ions; nanocellulose and SiO2-nanotubes are both porous structures with high specific surface area and porosity, so they have good physical adsorption properties and chemical reaction activity, which can adsorb and fix free manganese ions to achieve the purpose of intercepting the dissolution of manganese ions; BHA is grafted on the surface of nanocellulose, which contains a large amount of phenolic hydroxyl and tert-butyl groups. The phenolic hydroxyl group can reduce the negative impact of free radicals on the battery; the tert-butyl group can hinder the approach of other groups or molecules, further intercepting manganese ions, and thus improving the electrochemical performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron manganese phosphate positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of the new energy vehicle industry, the demand for power batteries has increased significantly, and the requirements for driving range have also continued to increase. Lithium iron manganese phosphate cathode materials have attracted much attention due to their low price, strong safety, high cycle stability and environmental friendliness, but their low energy density restricts their application in new energy electric vehicles. In this context, lithium iron manganese phosphate, as an upgraded alternative material to lithium iron phosphate, has become a cathode material that has attracted much attention in the market due to its advantages such as high energy density and high safety.

[0003] Lithium manganese iron phosphate not only uses Fe and Mn, two relatively low-cost metal elements, but also has a stable olivine structure, which has advantages in material cost and safety. However, the one-dimensional channel in the olivine structure of this material will limit the transmission efficiency of ions and electrons. In addition, Mn 2+ During the battery cycle, the Jahn-Teller effect may dissolve and deposit, which not only forms a manganese-deficient phase that hinders Li + The embedding and de-embedding of Li also destroys the solid electrolyte interface film (SEI film), resulting in the loss of active Li, thus affecting the cycle life of the battery. Summary of the invention

[0004] The purpose of the present invention is to provide a lithium manganese iron phosphate positive electrode material and a preparation method thereof to solve the following technical problems:

[0005] How to reduce the Mn content in lithium manganese iron phosphate positive electrode materials 2+ Dissolution rate during battery cycling.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a lithium manganese iron phosphate positive electrode material, which comprises 85-95 parts by weight of LiMn (1-X) Fe X PO4 and 3-8 parts of interception membrane material, wherein 0.9≥X≥0.7, the interception membrane material is composed of phenolic nanocellulose and SiO2-nanotubes in a mass ratio of 1:1; LiMn (1-X) Fe X The surface of PO4 has a carbon coating layer, and the interception membrane material is fixed on the surface of the carbon coating layer in the form of a thin film.

[0008] Preferably, LiMn (1-X) Fe XIn PO4, X=0.8.

[0009] Preferably, LiMn (1-X) Fe X PO4 is 90 parts and interception membrane material is 5 parts.

[0010] Because nanocellulose has high strength and modulus, its specific strength and modulus are more than 5 times that of steel, and it has excellent mechanical properties. It is also a degradable material that can be rapidly degraded in the environment without polluting the environment. The nanoscale size effect gives nanocellulose a large specific surface area and surface energy, which gives it good physical adsorption properties and chemical reaction activity. It also has a three-dimensional dynamic nanofiber network structure, which enables it to efficiently fix other nanoparticles or molecules, ions, etc.

[0011] Furthermore, the preparation method of the phenolic nanocellulose is:

[0012] Step A1, dissolving nanocellulose in ethanol, ultrasonically dispersing for 30 minutes to uniformly disperse the nanocellulose in the ethanol, then centrifuging to remove excess ethanol and impurities to form a nanocellulose dispersion with a solid content of 25-35%, transferring the nanocellulose dispersion to a magnetic stirrer, adding butylated hydroxyanisole (BHA) to the nanocellulose dispersion, adding sulfuric acid as a catalyst, adjusting the pH value of the solution to 5, stirring and reacting at 60° C. for 4 hours to obtain a reaction solution; wherein the amount ratio of nanocellulose to BHA is 1:2;

[0013] Step A2: centrifuge the obtained reaction solution to separate the product, repeatedly wash the product with ethanol to remove the residual catalyst and impurities, and send the washed product to a vacuum drying oven at 60° C. for 10-12 hours to obtain phenolic nanocellulose.

[0014] Through the above preparation method, BHA can be successfully grafted onto the surface of nanocellulose, so that the obtained phenolic nanocellulose has stronger antioxidant and stability. Free radicals in batteries are highly reactive molecules or atomic groups that can attack chemical bonds in battery materials, leading to material degradation and performance degradation. Free radicals attacking polymer electrolyte membranes may even cause the electrolyte membrane to become thinner or even perforated, seriously affecting the service life and performance of the battery. In addition, free radicals may also cause catalyst poisoning, resulting in a significant decline in battery performance. BHA contains a large number of phenolic hydroxyl groups, which can react with free radicals to form stable compounds, thereby blocking the oxidation chain reaction and reducing the negative impact of free radicals on the battery.

[0015] BHA also contains a large amount of tert-butyl groups, which have a large steric hindrance, which means that the tert-butyl group occupies a large space in the molecule, thereby hindering the approach of other groups or molecules, making BHA less susceptible to attack by external factors (such as light, heat, oxygen, etc.), which helps to maintain the antioxidant properties and chemical stability of BHA.

[0016] Furthermore, the SiO2-nanotubes are prepared by a template method, and the specific preparation method is:

[0017] Step B1, dissolving 2,3-dihydroxysuccinic acid as a pore-forming agent in ethanol to form a mixed solution, adding ethyl silicate dropwise to the mixed solution and stirring evenly, and standing for 0.5 h to obtain a pre-liquid; wherein the amount ratio of 2,3-dihydroxysuccinic acid to ethanol is 1 g: 250 mL; the amount ratio of 2,3-dihydroxysuccinic acid to ethyl silicate is 1 g: 40 mL;

[0018] Step B2, add ammonia water to the forward liquid and stir evenly, the dosage ratio of 2,3-dihydroxysuccinic acid to ammonia water is 1g:80mL, and let it stand for 3 hours to obtain a gel. The gel is repeatedly washed with deionized water to remove 2,3-dihydroxysuccinic acid, and then transferred to a vacuum drying oven and dried at 80°C for 24 hours to obtain SiO2-nanotubes.

[0019] In the above process, the SiO2-nanotubes prepared by the template method are porous structures with high specific surface area and porosity, which can play a role in adsorbing and separating ions. The porous structure can increase the adsorption capacity and improve the separation efficiency.

[0020] Furthermore, the preparation method of the interception membrane material is: phenolic nanocellulose and SiO2-nanotubes are blended and then ground to obtain a nanoscale two-component interception membrane material.

[0021] Furthermore, the LiMn (1-X) Fe X The preparation method of PO4 is:

[0022] Step C1, preparing a lithium source, a manganese source, an iron source and a phosphorus source according to the molar stoichiometric ratio of Li, Mn, Fe and PO4, adding a carbon source with a mass fraction of 6%, and ball milling with anhydrous ethanol as a solvent, and forming a mixed powder after drying;

[0023] Step C2: preheat the mixed powder at 350°C for 4 hours under nitrogen protection, then calcine at 680°C for 8 hours, and grind into fine powder after cooling to room temperature to obtain LiMn with a carbon coating layer. (1-X) Fe X PO4.

[0024] Furthermore, in step C1, the lithium source includes one or more of lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium acetate (CH3COOLi), lithium phosphate (Li3PO4), and lithium dihydrogen phosphate (LiH2PO4). Preferably, the lithium source is Li2CO3.

[0025] Furthermore, in step C1, the manganese source includes one or more of manganese oxides (MnO2, MnO3, MnO7), manganese salts (MnC2O4, MnSO4, Mn(NO3)2, etc.); preferably, the manganese source is MnC2O4.

[0026] Furthermore, in step C1, the iron source includes one or more of iron oxides (FeO, Fe2O3, Fe3O4), iron salts (FeCl3, Fe2(SO4)3, Fe(NO3)3); preferably, the iron source is FeCl3.

[0027] Furthermore, in step C1, the phosphorus source includes one or more of phosphoric acid (H3PO4), ammonium phosphate ((NH4)3PO4), and diammonium phosphate (NH4H2PO4); preferably, the phosphorus source is H3PO4.

[0028] Furthermore, in step C1, the carbon source includes one or more of sucrose, glucose, carbon black, polyethylene glycol, and polyvinyl alcohol; preferably, the carbon source is glucose.

[0029] In a second aspect, the present invention further discloses a method for preparing the lithium manganese iron phosphate positive electrode material as described above, comprising the following steps:

[0030] S1. Dissolve the interception membrane material in isopropanol to form an interception membrane solution. The ratio of the interception membrane material to isopropanol is 1g:(15-20)mL. Then (1-X) Fe X PO4 was added to the interception membrane solution and ultrasonically mixed for 1 h to make LiMn (1-X) Fe X PO4 is evenly dispersed in the interception membrane solution to obtain a mixed slurry;

[0031] S2, adding the mixed slurry into a vacuum filtration device, treating it at a vacuum degree of 0.05MPa for 2.5-3h, so that the phenolic nanocellulose and SiO2-nanotubes in the interception membrane solution are separated from the LiMn (1-X) Fe X The carbon coating layers of PO4 are intertwined and tightly combined on the surface to form a uniform film, thus obtaining a coarse material of lithium manganese iron phosphate positive electrode material;

[0032] S3, freezing the coarse material, and then transferring it to a freeze dryer for drying to remove the residual solvent, and then transferring it to a grinder for grinding and refining to obtain a lithium manganese iron phosphate positive electrode material.

[0033] In the above preparation process, the three-dimensional dynamic nanofiber network structure in nanocellulose can fix SiO2-nanotubes, and under vacuum filtration, the two are entangled and combined with each other, thereby (1-X) Fe X A thin interception film is formed on the surface of the carbon coating of PO4, which can improve the mechanical strength of the carbon coating. At the same time, the nanocellulose and SiO2-nanotubes in the interception membrane are porous structures with high specific surface area and porosity. Manganese ions are hindered from entering the porous structure, so manganese ions can be intercepted. SiO2-nanotubes contain BHA, which contains a large amount of phenolic hydroxyl and tert-butyl groups. Phenolic hydroxyl groups can react with free radicals to form stable compounds, thereby blocking the oxidation chain reaction and reducing the negative impact of free radicals on the battery. The tert-butyl group has a large steric hindrance, which can hinder the approach of other groups or molecules, further intercepting manganese ions and thereby improving the service life of the battery.

[0034] Beneficial effects of the present invention:

[0035] 1. In the lithium manganese iron phosphate positive electrode material of the present invention, a thin film formed by an interception membrane material is covered on the surface of the carbon coating layer. The interception membrane material includes nanocellulose and SiO2-nanotubes. The nanocellulose can fix the SiO2-nanotubes through a three-dimensional dynamic nanofiber network structure. Under vacuum filtration, the two are entangled and combined with each other to form the film. The nanocellulose has a high strength of more than 1000MPa and a high modulus of more than 60GPa. Therefore, the film has excellent mechanical properties, which can improve the mechanical strength of the carbon coating layer and prevent the dissolution of manganese ions.

[0036] 2. The nanocellulose and SiO2-nanotubes in the interception membrane material are both porous structures with high specific surface area and porosity, so they have good physical adsorption properties and chemical reaction activity, which can adsorb and fix free manganese ions to achieve the purpose of intercepting the dissolution of manganese ions.

[0037] 3. The surface of the nanocellulose in the interception membrane material is grafted with BHA, which contains a large amount of phenolic hydroxyl and tert-butyl groups. The phenolic hydroxyl group can react with free radicals to form stable compounds, thereby blocking the oxidation chain reaction and reducing the negative impact of free radicals on the battery; the tert-butyl group has a large steric hindrance, which can hinder the approach of other groups or molecules, further intercept manganese ions, and thus increase the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The present invention will be further described below in conjunction with the accompanying drawings.

[0039] Figure 1 It is a charge transfer resistance curve of the battery of lithium iron manganese phosphate positive electrode material prepared in Examples 1-3 of the present invention and Comparative Examples 1-4;

[0040] Figure 2 It is a capacity retention rate curve diagram of batteries of lithium manganese iron phosphate positive electrode materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0043] Preparation Example 1

[0044] Preparation of LiMn 0.2 Fe 0.8 PO4:

[0045] Step 1: Prepare Li2CO3, MnC2O4, FeCl3 and H3PO4 (the mass fraction of the four materials is 94% of the total material) according to the chemical molar ratio of n(Li):n(Mn):n(Fe):n(PO4)=1:0.2:0.8:1, add them into the ball mill, then add 6% (of the total material) of glucose and use anhydrous ethanol as solvent to form a grinding slurry (solid content 50%), the ball-to-material ratio is 20:1, put the ball mill on the ball mill for 5h, and then transfer it to a vacuum drying oven and dry it at 120℃ for 10h to form a mixed powder (LiMn 0.2 Fe 0.8 PO4 precursor);

[0046] Step 2: Transfer the mixed powder into a sintering machine, preheat at 350°C for 4 hours under nitrogen protection, calcine at 680°C for 8 hours, cool to room temperature and grind into fine powder to obtain LiMn with a carbon coating layer. 0.2 Fe 0.8 PO4.

[0047] Preparation Example 2

[0048] Preparation of phenolic nanocellulose:

[0049] Step 1: Add 10 g of nanocellulose to an ultrasonic stirrer containing 100 mL of ethanol and ultrasonically disperse for 30 minutes, then transfer to a centrifuge for centrifugal treatment to form a nanocellulose dispersion with a solid content of 30%, transfer the nanocellulose dispersion to a magnetic stirrer, add 20 g of BHA, and then add sulfuric acid dropwise to adjust the pH value of the system to 5, stir and react at 60° C. for 4 hours to obtain a reaction solution;

[0050] Step 2: The obtained reaction solution is transferred to a centrifuge for centrifugal treatment to separate the product, and the product is repeatedly washed with ethanol. The washed product is sent to a vacuum drying oven and dried at 60° C. for 11 hours to obtain phenolic nanocellulose.

[0051] Preparation Example 3

[0052] Preparation of SiO2-nanotubes:

[0053] Step 1: Add 4 g of 2,3-dihydroxysuccinic acid to 1000 mL of ethanol and stir to form a mixed solution, add 160 mL of ethyl silicate dropwise to the mixed solution and stir to form a mixed solution, and let stand for 0.5 h to obtain a pre-liquid;

[0054] Step 2: Add 320 mL of ammonia water to the forward liquid and stir evenly. Let it stand for 3 hours to obtain a gel. Wash the gel repeatedly with deionized water and then transfer it to a vacuum drying oven and dry it at 80°C for 24 hours to obtain SiO2-nanotubes.

[0055] Preparation Example 4

[0056] Preparation of interception membrane materials:

[0057] The same weight of phenolic nanocellulose and SiO2-nanotubes were blended and ball-milled for 3 hours to obtain a nanoscale two-component interception membrane material.

[0058] Comparative Preparation Example 1

[0059] Preparation of interception membrane materials:

[0060] The same weight of nanocellulose and SiO2-nanotubes were blended and ball-milled for 3 hours to obtain a nanoscale two-component interception membrane material.

[0061] Example 1

[0062] Step 1: Dissolve 5 g of the interception membrane material prepared in Preparation Example 4 in a beaker containing 100 mL of isopropanol and stir evenly to form an interception membrane solution. Then transfer the interception membrane solution into an ultrasonic stirrer and add 90 g of LiMn prepared in Preparation Example 1. 0.2 Fe0.8 PO4 was ultrasonically mixed for 1 h to obtain a mixed slurry;

[0063] Step 2: Add the mixed slurry into a vacuum filtration device and treat it at a vacuum degree of 0.05 MPa for 2.8 hours to obtain a coarse material of lithium manganese iron phosphate positive electrode material;

[0064] Step 3: Freeze the coarse material, then transfer it to a freeze dryer for drying, and then transfer it to a grinder for grinding to obtain a lithium manganese iron phosphate positive electrode material.

[0065] Example 2

[0066] Preparation of lithium manganese iron phosphate positive electrode material:

[0067] Step 1: Dissolve 3 g of the interception membrane material prepared in Preparation Example 4 in a beaker containing 60 mL of isopropanol and stir evenly to form an interception membrane solution. Then transfer the interception membrane solution into an ultrasonic stirrer and add 85 g of LiMn prepared in Preparation Example 1. 0.2 Fe 0.8 PO4 was ultrasonically mixed for 1 h to obtain a mixed slurry;

[0068] Step 2 is exactly the same as step 2 in Example 1;

[0069] Step 3 is exactly the same as step 3 in Example 1, and finally a lithium manganese iron phosphate positive electrode material is obtained.

[0070] Example 3

[0071] Step 1: Dissolve 8 g of the interception membrane material prepared in Preparation Example 4 in a beaker containing 120 mL of isopropanol and stir evenly to form an interception membrane solution. Then transfer the interception membrane solution into an ultrasonic stirrer and add 95 g of LiMn prepared in Preparation Example 1. 0.2 Fe 0.8 PO4 was ultrasonically mixed for 1 h to obtain a mixed slurry;

[0072] Step 2 is exactly the same as step 2 in Example 1;

[0073] Step 3 is exactly the same as step 3 in Example 1, and finally a lithium manganese iron phosphate positive electrode material is obtained.

[0074] Comparative Example 1

[0075] Compared with Example 1, the only difference is that the interception membrane material prepared in Preparation Example 4 is replaced by the interception membrane material prepared in Comparative Preparation Example 1, and other conditions remain the same, and finally a lithium manganese iron phosphate positive electrode material is prepared.

[0076] Comparative Example 2

[0077] Compared with Example 1, the only difference is that the interception membrane material prepared in Preparation Example 4 is replaced by the phenolic nanocellulose prepared in Preparation Example 2, and other conditions remain the same, and finally a lithium manganese iron phosphate positive electrode material is prepared.

[0078] Comparative Example 3

[0079] Compared with Example 1, the only difference is that the interception membrane material prepared in Preparation Example 4 is replaced by the SiO2-nanotube prepared in Preparation Example 3, and other conditions remain the same, and finally a lithium manganese iron phosphate positive electrode material is prepared.

[0080] Comparative Example 4

[0081] Directly use the LiMn prepared in Preparation Example 1 0.2 Fe 0.8 PO4 is used as the positive electrode material of lithium manganese iron phosphate.

[0082] Experimental testing

[0083] The lithium iron manganese phosphate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-4 were respectively made into batteries for testing of electrochemical properties. The preparation method was as follows: 90g of lithium iron manganese phosphate positive electrode material, 5g of Super-P, and 5g of polyvinylidene fluoride were mixed evenly, and then 200g of N-methylpyrrolidone solvent was added, and the mixture was mixed evenly to obtain a black slurry. The aluminum foil was placed in a coating machine, and the black slurry was poured in. After evenly coating, the slurry was transferred to an oven and dried at 40°C for 4h. The dried aluminum foil was then placed in a punching machine, and several pole pieces containing active substances were punched out and weighed. The pole pieces were placed in a drying bottle, and the pole pieces were transferred to a vacuum drying oven and dried at 110°C for 6h. Finally, the button batteries were assembled in a vacuum glove box.

[0084] Then, the prepared button battery was subjected to electrochemical performance tests, its charge transfer resistance was tested using an electrochemical workstation, and its capacity retention rate was tested using a constant current-constant voltage charge-discharge method. Figure 1-2 The test results are based on the first cycle capacity. Due to the polarization of the material, during the slow release of active lithium, after the first few cycles of activation, the capacity will slowly increase. Therefore, the capacity retention rate will show a climbing process in the early stage, that is, the capacity retention rate exceeds 100%.

[0085] The test results are listed in Table 1, which is as follows:

[0086]

[0087] By analyzing the data in Table 1, it can be seen that the batteries made of the lithium iron manganese phosphate positive electrode materials obtained in Examples 1-3 have significantly higher charge transfer resistance and capacity retention rate than those of Comparative Examples 1-4, which shows that the lithium iron manganese phosphate positive electrode material of the present invention achieves the purpose of reducing the dissolution of manganese ions and has stronger electrochemical properties.

[0088] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A lithium manganese iron phosphate positive electrode material, characterized in that: In parts by weight, including 85-95 parts of LiMn (1-X) Fe X PO4 and 3-8 parts of interception membrane material; Wherein, 0.9≥X≥0.7, the interception membrane material is composed of phenolic nanocellulose and SiO2-nanotubes in a mass ratio of 1:1; LiMn (1-X) Fe X The surface of PO4 has a carbon coating layer, and the interception membrane material is fixed on the surface of the carbon coating layer in the form of a thin film.

2. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The preparation method of the phenolic nanocellulose is: Step A1, dissolving nanocellulose in ethanol to form a nanocellulose dispersion, adding butylated hydroxyanisole to the nanocellulose dispersion, and then adding sulfuric acid as a catalyst, stirring and reacting at 60° C. for 4 hours to obtain a reaction solution; Step A2: centrifuge the obtained reaction solution to separate the product, wash and dry the product to obtain phenolic nanocellulose.

3. The lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: In step A1, the solid content of the nanocellulose dispersion is 25-35%, and the usage ratio of the nanocellulose to butylated hydroxyanisole is 1:

2.

4. The lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: In step A1, the amount of sulfuric acid used is the amount used when the solution reaches a pH of 5.

5. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The preparation method of the SiO2-nanotube is: Step B1, dissolving 2,3-dihydroxysuccinic acid in ethanol to form a mixed solution, adding ethyl silicate dropwise to the mixed solution and stirring evenly, and standing for 0.5 h to obtain a pre-liquid; Step B2, add ammonia water to the forward liquid and stir evenly, let it stand for 3 hours again to obtain a gel, wash and dry the gel to obtain SiO2-nanotubes.

6. The lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: The usage ratio of 2,3-dihydroxysuccinic acid to ethanol is 1 g:250 mL; the usage ratio of 2,3-dihydroxysuccinic acid to ethyl silicate is 1 g:40 mL; and the usage ratio of 2,3-dihydroxysuccinic acid to aqueous ammonia is 1 g:80 mL.

7. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The preparation method of the interception membrane material is: phenolic nanocellulose and SiO2-nanotubes are blended and then ground to obtain a nano-scale two-component interception membrane material.

8. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The LiMn (1-X) Fe X The preparation method of PO4 is: Step C1, preparing a lithium source, a manganese source, an iron source and a phosphorus source according to the molar stoichiometric ratio of Li, Mn, Fe and PO4, adding a carbon source with a mass fraction of 6%, and ball milling with anhydrous ethanol as a solvent, and drying to form a mixed powder, Step C2: preheat the mixed powder at 350°C for 4 hours under nitrogen protection, then calcine at 680°C for 8 hours, and grind into fine powder after cooling to room temperature to obtain LiMn (1-X) Fe X PO4.

9. A method for preparing a lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Dissolve the interception membrane material in isopropanol to form an interception membrane solution, and then (1-X) Fe X PO4 is added to the interception membrane solution and ultrasonically mixed to obtain a mixed slurry; S2, adding the mixed slurry into a vacuum filtration device, treating it at a vacuum degree of 0.05 MPa for 2.5-3 h to obtain a coarse material of lithium manganese iron phosphate positive electrode material; S3. The coarse material is freeze-dried and then ground into fine powder to obtain lithium manganese iron phosphate positive electrode material.

10. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 9, characterized in that: In step S1, the usage ratio of the intercepting membrane material to isopropanol is 1 g:(15-20) mL.

Citation Information

Patent Citations

  • Preparation method of lithium ferric manganese phosphate composite material and lithium ferric manganese phosphate composite material

    CN115974039A

  • Lithium manganese iron phosphate base material, positive electrode material, preparation methods of lithium manganese iron phosphate base material and positive electrode material and lithium battery

    CN117720086A